A style manual for the presentation of papers and theses in religion and theology - McIntosh, Lawrence D.; Charles Sturt University -Riverina. Centre for Information Studies; Australian and New Zealand Association of Theological Schools; Australian and New Zealand Theological Library Association (Wagga Wagga, NSW Centre for Information Studies, Charles Sturt University, 1994)
Includes bibliographical references and index.
Keywords: Theology -- authorship; Authorship -- style manuals; English language -- grammar -- 1950- -- handbooks, manuals, etc